2017
DOI: 10.1007/s00441-017-2598-8
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage type modulates osteogenic differentiation of adipose tissue MSCs

Abstract: Since the reconstruction of large bone defects remains a challenge, knowledge about the biology of bone healing is desirable to develop novel strategies for improving the treatment of bone defects. In osteoimmunology, macrophages are the central component in the early stage of physiological response after bone injury and bone remodeling in the late stage. During this process, a switch of macrophage phenotype from pro-inflammatory (M1) to anti-inflammatory (M2) is observed. An appealing option for bone regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 38 publications
16
150
1
Order By: Relevance
“…However, given the cell behavioural difference in 3D and 2D culture systems and the fact that 3D scaffolds are a crucial part of cell‐based bone constructs, we here established a direct 3D coculture system by using human primary ADMSCs, THP‐1 cells and electrospun scaffolds. In contrast to the previously observed stimulatory effects of macrophages on the osteogenic differentiation of ADMSCs (Zhang et al, ), monocytes, M1 macrophages, and M2 macrophages significantly inhibited the osteogenic differentiation of cocultured ADMSCs. This is evidenced by decreased ALP activity, mineralization content, and expression of several osteogenic markers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, given the cell behavioural difference in 3D and 2D culture systems and the fact that 3D scaffolds are a crucial part of cell‐based bone constructs, we here established a direct 3D coculture system by using human primary ADMSCs, THP‐1 cells and electrospun scaffolds. In contrast to the previously observed stimulatory effects of macrophages on the osteogenic differentiation of ADMSCs (Zhang et al, ), monocytes, M1 macrophages, and M2 macrophages significantly inhibited the osteogenic differentiation of cocultured ADMSCs. This is evidenced by decreased ALP activity, mineralization content, and expression of several osteogenic markers.…”
Section: Discussioncontrasting
confidence: 99%
“…Immunofluorescence images were acquired with a fluorescence microscope (Zeiss AxioCam MRc5, Carl Zeiss Microimaging GmbH, Germany), and the relative intensity of fluorescence was analysed using ImageJ (U.S. National Institutes of Health, Bethesda, USA). The value of red (Alexa 568) and green (Alexa 488) fluorescence of each sample was further normalized for the value of blue fluorescence (DAPI), as described previously (Zhang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the scarce reports available on the role of macrophages in MSC recruitment, the role of macrophages in osteogenic differentiation of MSCs was intensively studied. Although the importance of M1 macrophage-associated molecules (i.e., OSM, TNF-α, and IL-6) for bone repair was convincingly demonstrated using animals deficient in these molecules (11,(31)(32)(33); data from other in vitro studies concerning the relative role of M1 and M2 macrophages in MSC osteogenic differentiation were not consistent (11)(12)(13)34). We reasoned that this inconsistency of the data obtained from in vitro osteogenic differentiation assays might be caused by the experimental setup in which most designs added either M1 or M2 macrophages into a coculture system that lasted 3-4 weeks.…”
Section: M1 Macrophages Secreted High Levels Of Osteogenic Proteins Amentioning
confidence: 96%
“…Implant surface properties, including roughness, chemistry, wettability, and surface charge, have been shown to influence the gene expression and/or secretion of several proinflammatory and anti‐inflammatory cytokines in monocultures of human monocytes or murine macrophages (Brodbeck et al, ; Hotchkiss et al, ). Besides, a recent study showed that direct co‐cultures of human macrophage cell line (THP‐1) with human MSC on tissue culture polystyrene resulted in significant changes in the number of adherent MSC and their mineralization capacity depending on the polarization (M1/M2) of the co‐cultured THP‐1 macrophages (Zhang et al, ). Therefore, it is crucial to explore if the coexistence of monocytes with MSC on implants with different surfaces will influence the cell–material and cell–cell interactions for both cell types in the co‐culture.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent study showed that direct co-cultures of human macrophage cell line (THP-1) with human MSC on tissue culture polystyrene resulted in significant changes in the number of adherent MSC and their mineralization capacity depending on the polarization (M1/M2) of the co-cultured THP-1 macrophages (Zhang et al, 2017). Therefore, it is crucial to explore if the coexistence of monocytes with MSC on implants with different surfaces will influence the cell-material and cell-cell interactions for both cell types in the co-culture.…”
mentioning
confidence: 99%